Memorandum of understanding between Universiti Teknologi MARA and Seni Warisan Artistic Consultant (SWA TV Media) / Fakulti Muzik - Universiti Teknologi MARA, Fakulti Muzik (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on friendship and cooperation for friendship, cooperation and collaboration.